A. find y' by implicit differentiation.

B. solve th equation explicitly for y and differentiate to get y' in terms of x.

cos (x) + √y = 5

1 answer

a)
- sin(x) + (1/2)y^(-1/2)dy/dx = 0
-(1/4)(1/√y)dy/dx = sin(x)

dy/dx = -4√y sin(x)

b)
√y = 5 - cosx
y = 25 - 10cosx + cos^2 x
dy/dx = -10cosx + 2(cosx)(-sinx)
= -2cosx(5cos(x) + 2sin(x))
Similar Questions
  1. Using 4x^2 - 9y^2 = 36Find y by implicit differentiation and then solve the equation explicitly for y and differentiate to get
    1. answers icon 0 answers
  2. Using 4x^2 - 9y^2 = 36Find y by implicit differentiation and then solve the equation explicitly for y and differentiate to get
    1. answers icon 1 answer
  3. Consider the following.cos(x) + sqrt(y)= 1 (a) Find y' by implicit differentiation. y' = 2y^(1/2) sin(x) Correct: Your answer is
    1. answers icon 4 answers
  4. If cos(3 x)�6Ó14 x e^2 y=0, find [ dy/dx] using implicit differentiation.In this problem, you should differentiate both sides
    1. answers icon 0 answers
more similar questions